Morphometric allometry of horseshoe crab, Tachypleus gigas at west part of Sarawak waters, Borneo, East Malaysia - A. Raman, Noor Jawahir; Mohd L., Shabdin; Mohamad, Samsur; Khairul-Adha, A. Rahim (Bioflux SRL, 2017)
A study was conducted at west part of Sarawak waters in Borneo, Malaysia to compare the morphometric allometry of coastal horseshoe crab, Tachypleus gigas obtained from two different locations, Pasir Putih Village and Gerigat Beach. The specimens were collected by using hand manually and monofilament gill netting during March 2014 to April 2014. All measurements of body parameters of male and female T. gigas from Gerigat Beach were recorded higher compared to specimens from Pasir Putih Village. All body parameters between male and female T. gigas from both locations showed significant different when p < 0.05. Allometric analysis was used to compare BW-TL/CW of T. gigas in log transform by using Pearson correlation and regression analysis. Male and female T. gigas from both locations revealed negative allometric growth for all body parameter relationships since ‘b’ value was less than 3 excluding BW-CW and TEL-TL of female from Gerigat Beach. Two way ANCOVA analysis indicated significant differences in BW-CW and BL-TL relationships of both sexes from two locations. The dissimilar size of T. gigas from different locations in west Sarawak waters is probably due to two discrete populations